WONDERFUL HARMONY OF COLORS IN NATURE ILLUSTRATION RAMKUMAR: प्रकृति चित्रण में रंगों का अद्भुत सामंजस्य-कलाकार रामकुमार - Sharma, Rita (International Journal of Research -GRANTHAALAYAH, 2014)
Characters have an important place in human life as well as in painting. Varna is the essence of human life and pictures, just as words are needed for poetry, rhythm for music and juice for poetry, similarly color is essential for pictures. In the absence of color, the picture is monotonous, so from primitive cavities to the present day, artists have been taking the shelter of colors and expressing their souls. In the Indian painting conspiracy, cohesion is referred to as the name Variak Bhang. The possible mixing of colors in the picture is actually a color breakdown. Objects have knowledge of the nature, atmosphere and meaning of the picture only through colors. That is why the artist either uses the same color as the external meaning or makes pictures based on the symbolic analogy while planning the picture of the picture. is. If we study colors in painting today, then it is known that the artist uses colors to suit his inner mind. मानव जीवन के साथ-साथ चित्रकला में वर्ण का महत्वपूर्ण स्थान है। वर्ण मानव जीवन एंव चित्र का सार है जिस प्रकार कविता के लिये शब्द, संगीत के लिये लय तथा काव्य के लिये रस की आवश्यकता हाती है, उसी प्रकार चित्र के लिये रंग का होना अनिवार्य है। रंग के अभाव में चित्र नीरस है इसलिए आदिम गुहावासियों से लेकर आज तक कलाकार रंगों का आश्रय लेकर आत्माभिव्यक्ति करता आया है। भारतीय चित्र षडंग में वर्ण-सामांजस्य को वर्णिका भंग नाम से सम्बोधित किया गया है। चित्र में रंगों की यथा सम्भव मिली-जुली भंगिमा वास्तव में वर्णिका भंग है। वस्तुओं में रंगों के माध्यम से ही चित्र के स्वभाव, वतावरण तथा अर्थ का ज्ञान होता है यही कारण है कि चित्र का वर्ण नियोजन करते हुये कलाकार या तो बाह्य यर्थाथ के समान रंगों का प्रयोग करता है या प्रतीकात्मक सादृश्य के आधार पर चित्रों की रचना करता है। यदि आज चित्रकला में रंगों का अध्ययन करे तो यह ज्ञात होता है कि कलाकार अपने अन्र्तमन के अनुरूप रंगों का प्रयोग करता है।